Anthropological study of Afghan Festivals and celebrations based on cultural dimensions as learning media - Enayatullah Dadman (Journal of diversity in learning (JDIL), 2022)
Tradition is an important area of ​​popular and folk culture, due to the cutting-edge significance given to lifestyle and lifestyle, great efforts have been invested in the maintenance and development of such festivals. However, as an expression of the universe, the view of the arena put forward by the galas can sometimes clash with modern social values, which soon correlate with the difficulty of human beings living together in harmony. The purpose of this case study is that the anthropology of festivals and celebrations can be used as a medium for learning history by reconstructing festival activities. This unique culture may also encompass not only the simplest traditional folk festivals but also other festivals which, from a multiculturalist perspective, are being held more and more frequently in Afghanistan. although the aim of these festivals is to aid social integration, along with their views on lifestyle, they may, in fact, make a closer contribution to legitimizing social constructs that tend to favor hierarchical variations between natives and immigrants. we are confronted here with a paradox that demands a clean and essential attitude with the help of anthropologists. This article aims to analyze historical learning about Afghan festivals based on the cultural dimension so that the results show that Afghan festivals such as Nawruz, Nowruz tricks, Janda Bala, shahtoraha, and Samanak are cultural dimensions for Afghan society.